2017
DOI: 10.1212/nxg.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scan in Hispanics highlights candidate loci for brain white matter hyperintensities

Abstract: Objective:To investigate genetic variants influencing white matter hyperintensities (WMHs) in the understudied Hispanic population.Methods:Using 6.8 million single nucleotide polymorphisms (SNPs), we conducted a genome-wide association study (GWAS) to identify SNPs associated with WMH volume (WMHV) in 922 Hispanics who underwent brain MRI as a cross-section of 2 community-based cohorts in the Northern Manhattan Study and the Washington Heights–Inwood Columbia Aging Project. Multiple linear modeling with PLINK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Consistent with those genome-wide association studies and our previous replication study which aimed to verify the top risk variants identified in the first GWAS study in European population (Hofer et al, 2015; Huang et al, 2016; Traylor et al, 2016; Beecham et al, 2017), this study also did not find any significantly positive associations of those strongest and suggestive risk genes that were identified in the multi-ethnic GWAS with LA in this Chinese population. Even the strongest WMH-associated variant (rs7214628 located in TRIM65 gene in 17q25 locus) which holds the strongest significance of p < 2.7E-19 and p < 5.1E-19 in European individuals and multi-ethnic populations, respectively (Verhaaren et al, 2015), also showed a lack of significant and detrimental effect on LA in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with those genome-wide association studies and our previous replication study which aimed to verify the top risk variants identified in the first GWAS study in European population (Hofer et al, 2015; Huang et al, 2016; Traylor et al, 2016; Beecham et al, 2017), this study also did not find any significantly positive associations of those strongest and suggestive risk genes that were identified in the multi-ethnic GWAS with LA in this Chinese population. Even the strongest WMH-associated variant (rs7214628 located in TRIM65 gene in 17q25 locus) which holds the strongest significance of p < 2.7E-19 and p < 5.1E-19 in European individuals and multi-ethnic populations, respectively (Verhaaren et al, 2015), also showed a lack of significant and detrimental effect on LA in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Other single nucleotide polymorphisms including rs7214628 in TRIM65 and rs78857879 in EFEMP1 had also been verified at genome-wide significance level by one later genome-wide meta-analysis study in overall combined community populations with stroke patients of European ancestry (Traylor et al, 2016). However, most of those SNPs could not be replicated by three recently published GWAS studies in independent populations (such as whites of European descent, African Americans, or Hispanic participants) to date (Hofer et al, 2015; Traylor et al, 2016; Beecham et al, 2017). On the contrary, they identified a large number of novel WMH-associated loci including four genome-wide significant genes ( NBEAL1 , EVL , C1QL1 , and COL4A2 ) and 12 suggestive genes ( CDC7 , ST6GAL2 , GATA6 , GFRA4 , TRIM6 , WFDC3 , FAM118A , UBE2C , PTPLA , RGPD4 , ALMS1 , and ZNF280D ), as well as four suggestive variants (rs10883817 in the introns of AS3MT , CNNM2 , and NT5C2 ; rs4761974 in close proximity to SLC4A8 ; rs6135309 in the intron of MACROD2 ; and rs7664442 located in the intergenic region near GBA3 ) (Hofer et al, 2015; Traylor et al, 2016; Beecham et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although large-scale genetic studies of European descendants have identified many risk genes and single nucleotide polymorphisms (SNPs) in European descent, a small amount of SNPs from those risk genes has been confirmed in cross-ethnic genetic studies [ 22 , 24 , 25 , 27 , 29 35 ]. This not only indicates significant ethnic differences in LA susceptibility but also suggests a limited contribution from SNPs to LA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers across the USA have contributed significantly to the field of Latinx health and aging and continue to build evidence in this area (Table 1). For example, longitudinal studies of diverse populations have included non-demented Latinxs along with non-Latinx blacks and whites to examine stroke and related risk factors [9][10][11], as well as aging and incident dementia [9,[12][13][14][15]. Research has also focused on blood biomarkers of older Latinxs from select countries of origin with and without a diagnosis of mild cognitive impairment (MCI) or Alzheimer's dementia [4,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Through 5 cohort studies, the Rush Alzheimer's Disease Center (RADC) [8][9][10] aims to conceptualize and conduct needed studies of older adults across diverse racial and ethnic groups. The foundation for partnering with older Latinxs, in particular, began with our earliest cohort study, the Religious Orders Study (ROS) [34].…”
Section: Introductionmentioning
confidence: 99%